Variation of nucal scutellation pattern of American crocodile (Crocodylus acutus Cuvier 1807) in La Ventanilla, Oaxaca, Mexico. - García-Grajales, Jesús; Buenrostro Silva, Alejandra; Téllez-Rodríguez, Penélope R. (Instituto de Ecología, A.C., 2009)
The post-occipital and nucal scutellation patterns of 111 crocodiles (Crocodylus acutus) from La Ventanilla, Oaxaca were analyzed. Thirty three different scutellation patterns were found. The most frequently observed pattern (31.5%) was 4 post-occipital scales present 2 external previous nucal scales absent, and 2 posterior nucal scales present (4-2EE-2). The pattern considered typical for this species was observed only in 6.31% of individuals. There were differences between the frequency distribution of common patterns when compared to other studies on C. acutus.